Pelatihan Pengembangan Media Interaktif Berbasis Genially Bagi Guru di SMKN 1 Mootilango - Masra Latjompoh; Nurul Fajryani Usman (-, 2026)
Digital transformation requires teachers to develop interactive learning media that suit the characteristics of vocational education. This community service program aimed to improve the knowledge and skills of teachers at SMKN 1 Mootilango in developing Genially-based interactive media. The program employed a participatory, practice-based approach through needs analysis, material presentation, genially demonstrations, guided practice, product presentation and revision, evaluation, and reflection. The results showed that teachers gained a better understanding of interactive media principles and were able to develop learning media integrating text, images, videos, animations, navigation buttons, links, and quizzes. The program also encouraged greater confidence, openness to technology, and collaboration among teachers. The resulting media offered advantages in visual quality, interactivity, flexibility, and ease of distribution, although their use still depended on adequate devices and internet access. This training represents an initial step toward strengthening teachers’ digital competence and fostering an innovative learning culture at school.